More Haste, Less Speed: Could Public–Private Partnerships Advance Cellular Immunotherapies? - Bubela, Tania; Bonter, Katherine; Lachance, Silvy; Delisle, Jean-Sébastien; Gold, E. Richard (Frontiers in Medicine, 2017)
Cellular immunotherapies promise to transform cancer care. However, they must overcome serious challenges, including: (1) the need to identify and characterise novel cancer antigens to expand the range of therapeutic targets; (2) the need to develop strategies to minimize serious adverse events, such as cytokine release syndrome and treatment-related toxicities; and (3) the need to develop efficient production/manufacturing processes to reduce costs. Here we discuss whether these challenges might better be addressed through forms of public-private research collaborations, including public-private partnerships, or whether these challenges are best addressed by way of standard market transactions. We analysed fourteen public-private relationships and 25 underlying agreements for the clinical development of cancer cellular immunotherapies in the United States. Most were based on bi-lateral research agreements and pure market transactions in the form of service contracts and technology licenses, which is representative of commercialization focus of the field. We make the strategic case that multi-party public-private partnerships may better advance cancer antigen discovery and characterization and improved cell processing/manufacturing and related activities. In the rush towards the competitive end of the translational continuum for cancer cellular immunotherapy and the attendant focus on commercialization, many gaps have appeared in our understanding of cellular biology, immunology, and bio-engineering. We conclude that the model of bi-lateral agreements between leading research institutions and the private sector may be inadequate to efficiently harness the interdisciplinary skills and knowledge of the public and private sectors to bring these promising therapies to the clinic for the benefit of cancer patients.